Life-long perspective in development of a project manager - Mikhieieva, Olga (КНУБА, 2016)
The life cycle of a project manager is usually described by the roles played in a project and often framed within one of the leading professional project management (PM) organizations. Nevertheless, the development of project managers is by nature many-sided and it might deviate from linear progressive education and career. The life-long perspective is an important aspect of project manager’s development, as its dynamics often lasts till the very end of the professional life cycle. Project manager’s development can be described in such directions as academic, professional, and personal. In this paper, the author highlights the significant role of life-long learning and those aspects of education, development, and experience, which are relevant for life-long learning in project management; as well as the need to empower such learning which can be addressed though the available PM practices.
Keywords: life-long learning; project manager’s development; career path; knowledge and skills; 005.8; 005.1